Association of bone mineral density and depression in different bone sites and ages: A meta‐analysis. Issue 9 (19th July 2021) - Yuan, Shiyi; Chen, Jianjun; Zeng, Li; Zhou, Chanjuan; Yu, Shenrun; Fang, Liang
Abstract: Major depressive disorder (MDD) is considered as a risk factor for osteoporosis. Bone mineral density (BMD), as the main tool for diagnosing osteoporosis, has been reported to have correlation with MDD in different cohorts. However, the information in causative link and etiology determinants of osteoporosis in MDD is still under investigation. The results are unclear. Thus, we perform a meta‐analysis to evaluate the association between altered BMD and MDD. We searched the electronic databases to find studies examining BMD in patients with MDD. Finally, 26 published studies were included in our meta‐analysis up from January 1990 to January 2019. All the data were pooled analysis using RevMan software. The association between altered BMD and MDD was assessed by std. mean difference (STD) and their 95% confidence intervals (CIs) for each study. Twenty‐six studies were included in this meta‐analysis. Pooled results showed a significant lower BMD in spine (STD=0.51, 95% CI=0.30–0.71, p < .00001), total hip (STD=0.41, 95% CI=0.16 to 0.66, p = .001), and femoral neck (STD=0.93, 95% CI=0.32 to 1.55, p = .003) in MDD compared with controls. After stratification by mean age, gender, recruitment, diagnostic criteria, and measuring methods, no significant difference of BMD was found in bone mineral density of male total hip between MDD and controls( p > .05). Moreover, adults appear to have lower BMD than old cohorts. This is an updated meta‐analysis to reveal the association of bone mineral density and depression, suggesting that BMD appears to be more susceptible to occur in spine, total hip, femoral neck in MDD, especially for adults and women. Our meta‐analysis may provide clinicians and public health administrators with an important screening tool for assessing depression and avoiding osteoporosis in adult subjects and female. Abstract : Work flow of meta‐analysis.